Application of AHP to Multi-Item Inventory Management Using Part Period Algorithm - Hossein Jamshidi; Emeka Dunu; Guy Posey (Journal of Management Research, 2024)
This empirical study deals with integration of Analytical Hierarchy Process (AHP) with multi-item inventory management using Part-Period Algorithm. Among many variables which affects inventory systems, this study considers the variables of lot-sizing rules, sequencing, demand pattern, coefficient of variations, and change over cost. AHP is used to pick a sequencing rule and performance criteria. This study describes the application of AHP methodology in the form of multiple tables that will assist production managers in a Group Technology environment, to minimize employee and machine idleness. It will help managers make decisions on production order quantity, the sequence in which jobs should enter work centers, and in the determination of uniform production cycle times.